Encyclopedia of Structural Health Monitoring 2008
DOI: 10.1002/9780470061626.shm144
|View full text |Cite
|
Sign up to set email alerts
|

Lamb Wave‐BasedSHMfor Laminated Composite Structures

Abstract: This article examines the application of low‐frequency Lamb waves for the detection of delaminations (interlaminar cracking) in thick composite laminates. Surface‐mounted piezoelectric devices are excited with a tone burst of a few cycles generating a stress wave that propagates along the structure. Experiments carried out on composite beam specimens are discussed where wave propagation distances over 2 m are achieved and delaminations as small as 1 cm 2 are successfully identified. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…2D FE simulations and experimental studies showed that the power transmission of Lamb waves can be used to evaluate the integrity of the repair patches. Soutis and Diamanti [21] demonstrated the use of Lamb waves to inspect adhesively bonded patch repaired composite laminates. The study specifically focused on the low frequency fundamental anti-symmetric (A 0 ) Lamb wave.…”
Section: Lamb Waves In Complex Structures Made By Compositementioning
confidence: 99%
“…2D FE simulations and experimental studies showed that the power transmission of Lamb waves can be used to evaluate the integrity of the repair patches. Soutis and Diamanti [21] demonstrated the use of Lamb waves to inspect adhesively bonded patch repaired composite laminates. The study specifically focused on the low frequency fundamental anti-symmetric (A 0 ) Lamb wave.…”
Section: Lamb Waves In Complex Structures Made By Compositementioning
confidence: 99%
“…As discussed in Sec. I.B, a number of studies have modelled these joints and repaired composite laminates using similar approaches [33][34][35][36] . As shown in Fig 1, the centre of a 22 mm wide structural feature was located at x  0 mm.…”
Section: Three-dimensional Finite Element Simulationsmentioning
confidence: 99%